Public Debt in Advanced Economies and its Spillover Effectson Long-Term Yields - Alper, Emre (IMF Working Papers; Working Paper ;, 2011)
Several models establish a positive association between public debt ratios and long-term real yields, but the empirical evidence is not always conclusive. We reconsider this issue, focusing in particular on possible spillover effects of large advanced economies' debt levels to other economies' borrowing yields, especially in emerging markets. We extend the existing literature by using real time expectations of fiscal and other macroeconomic variables for a large sample of advanced and emerging economies. We show that an increase in the public debt levels of large advanced economies - especially the United States - spills over to both emerging markets and other advanced economies' long-term real yields and that this effect is significant at the current levels of advanced economies' debt ratios.